Optimising tetrazolium test procedures to evaluate the physiological potential of peanut seeds - Santos, J. F. [UNESP]; Sanches, M. F. G. [UNESP]; Barbosa, R. M. [UNESP]; Leao, E. F. [UNESP]; Vieira, Roberval Daiton [UNESP] (Ista-int Seed Testing Assoc, 2012)
The tetrazolium test stands out as an evaluation method in determining seed physiological potential due to the diversity of the information provided. Nonetheless, efficiency depends on following appropriate procedures, which have been lacking for peanut. The objective of the present study was to improve the efficiency and reliability of the tetrazolium test for peanut seeds. Eight seed lots, four of cv. IAC Tatu ST and four of cv. Runner IAC 886, were evaluated by germination and vigour tests (accelerated ageing and electrical conductivity), and seedling emergence in the field. For the tetrazolium test, seeds were preconditioned at 25 degrees C for 3, 6, 9, 12 and 16 hours immersed directly in water (cup) and 16 and 24 hours in moistened germination paper. After determining the best preconditioning period, seeds were prepared with seed coat, without seed coat and without seed coat with the cotyledons separated, followed by immersion in 0.05, 0.075, 0.1 and 0.2% tetrazolium solution at 40 degrees C for two hours. The best preconditioning treatment was 16 hours immersed directly in water. For differentiating seed lots, a 0.05% tetrazolium solution is recommended for cv. IAC Tatu ST (Valencia group) seeds with seed coat removal, and a 0.075% solution for cv. Runner IAC 866 (Virginia group) seeds without seed coat and separated cotyledons.